Microelements, pro- and anti-oxidant blood activity in arterial hypertension - A. R. Antonov; E. A. Vaskina; Yu. D. Chernyakin (Российский кардиологический журнал, 2006)
Ninety arterial hypertension (AH) patients were divided into three groups, by AH severity. Levels ofiMg, Ca, Cu, Zn, Fe, pro- and antioxidant blood activity (POA, AOA) were measured. Various disturbances, defined as «combined biometal dysbalance syndrome» were diagnosed. POA and AOA dynamics correlated with microelement (ME) status. Hypozincemia was caused by Zn reserve deficiency and myocardial accumulation. Increased Fe levels, correlating with AH stage, confirmed Fe metabolism cumulative theory. Active ME role in АО defense and AH pathogenesis was observed.